2018
DOI: 10.1177/1468798418754938
|View full text |Cite
|
Sign up to set email alerts
|

‘The pumpkins are coming…vienen las calabazas…that sounds funny’: Translanguaging practices of young emergent bilinguals

Abstract: In this paper, we utilize the theory of translanguaging to make sense of the biliterate activities of young emergent bilinguals in a before-school program for Latinx students at an elementary school. Our findings show that even early writers are able to draw from their full linguistic repertoire, utilizing orthographic and syntactic resources consciously, and continue to do so with increasing complexity as they get older and gain greater competence. The children in our study show how emergent bilinguals exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…One of the many challenges facing these young children is the disjuncture between their multilingual out-of-school and often monolingual in-school language and literacy practices. In Englishspeaking countries, particularly where schools adhere to 'English-only' policies (Axelrod and Cole 2018), longitudinal analyses suggest that children who speak a language other than English at home often experience a decline in heritage language use during early childhood, and heritage language loss after starting formal schooling (Verdon, McLeod, and Winsler 2014), which impacts negatively on familial relations and individuals' sense of identity (Wong Fillmore 2000). Multiple factors contribute to language loss including the lack of language input (Pearson 2007), the language choice of siblings (Pease-Alvarez 1993), pressure from preparation for schooling in English (Jordaan 2008), and low social status of the heritage language (Dixon, Wu, and Daraghmeh 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One of the many challenges facing these young children is the disjuncture between their multilingual out-of-school and often monolingual in-school language and literacy practices. In Englishspeaking countries, particularly where schools adhere to 'English-only' policies (Axelrod and Cole 2018), longitudinal analyses suggest that children who speak a language other than English at home often experience a decline in heritage language use during early childhood, and heritage language loss after starting formal schooling (Verdon, McLeod, and Winsler 2014), which impacts negatively on familial relations and individuals' sense of identity (Wong Fillmore 2000). Multiple factors contribute to language loss including the lack of language input (Pearson 2007), the language choice of siblings (Pease-Alvarez 1993), pressure from preparation for schooling in English (Jordaan 2008), and low social status of the heritage language (Dixon, Wu, and Daraghmeh 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In ways that resonated with developmental spelling and showcased their “double metalinguistic awareness” (Kenner et al, 2004), Abdul and Maya used English letter–sound correspondences to write in Urdu and Amharic. Their writing builds on existing research that suggests young Spanish/English bilingual children engage in this work (e.g., Axelrod & Cole, 2018; Durán, 2018), by demonstrating how children might repurpose English when writing in languages that use non-Roman scripts, such as Urdu and Amharic. Across their interviews, they expressed feelings of pride and relief as they experienced translingual writing instruction that made space for the breadth of their communicative repertoires.…”
Section: Resultsmentioning
confidence: 87%
“…For example, Durán (2017) examined bilingual children’s writing in an audience-focused curriculum, arguing that children made strategic languaging choices to connect with authentic audiences, including parents and a published bilingual author. In a before-school writing program designed to support the languaging practices of young bilingual students, Axelrod and Cole (2018) similarly found that children demonstrated an awareness of audience as they chose when and where to use Spanish in their writing to Mexican pen pals. They also found that young children noticed orthographic differences between English and Spanish as they composed, strategically choosing where to deploy features like consonant digraphs.…”
Section: Language and The Writing Classroommentioning
confidence: 98%
“…Cole 2018 brokering (Orellana, 2009), and cultural and linguistically diverse affinity (Martínez, 2010;Axelrod & Cole, 2018) Angie expressed that in her everyday language practice she believed that she didn't "mix…”
Section: Racialized Bilinguals On Translation: "I've Been Translatingmentioning
confidence: 99%